Backyard poultry farming in Sikkim with improved Vanaraja chicken - Babu, Subhash; Avasthe, R K; Singh, Raghavendra; Das, Samir (Indian Farming, 2015)
In Sikkim, more than 70% people possess agricultural background and 80% of these people keep livestock of different species as a supplementary source of income. Poultry is one of the quickest ways for rapid increase in protein supply in the short run. Backyard poultry with Vanaraja chicken may provide extra income and employment opportunities to the rural people, particularly for the weaker sections of the community. Backyard poultry with improved Vanaraja chicken may play a crucial role for fulfilling the demand for meat and eggs in the local market.